2021
DOI: 10.22515/jfib.v3i2.2970
|View full text |Cite
|
Sign up to set email alerts
|

Bank Wakaf Mikro Usaha Mandiri Sakinah: Pemberdayaan Ekonomi Perempuan Universitas Aisyiyah Yogyakarta

Abstract: Bank Wakaf Mikro (BWM) Usaha Mandiri Sakinah merupakan BWM pertama berbasis universitas di Indonesia. Di bawah naungan Universitas Aisyiyah (UNISA) Yogyakarta, BWM ini fokus pada penyediaan akses pembiayaan dan pemberdayaan perempuan pelaku usaha kecil dan mikro. Kegiatan pemberdayaan tesebut terwujud melalui program pelatihan dan pendampingan. Tulisan ini merupakan hasil analisis terhadap etos gerakan BWM Usaha Mandiri Sakinah. Bagaimana pandangan Aisyiyah memengaruhi gerakan BWM Usaha Mandiri Sakinah? Bagaim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Kebanyakan penelitian tentang BWM terkait dampak BWM dalam pengaruh perekonomian, seperti penelitian yang dilakukan oleh Dewanti et al, (2016) dan Zayanie et al, (2019). Maka, penelitian tentang sejauh mana niat nasabah menggunakan produk pembiayaan pada BWM dengan mencakup pengetahuan, religiusitas dan sikap menjadi penting untuk dilakukan.…”
Section: Pendahuluanunclassified
“…Kebanyakan penelitian tentang BWM terkait dampak BWM dalam pengaruh perekonomian, seperti penelitian yang dilakukan oleh Dewanti et al, (2016) dan Zayanie et al, (2019). Maka, penelitian tentang sejauh mana niat nasabah menggunakan produk pembiayaan pada BWM dengan mencakup pengetahuan, religiusitas dan sikap menjadi penting untuk dilakukan.…”
Section: Pendahuluanunclassified
“…Some research reported that microfinance institutions significantly impact women empowerment programs (Fitri et al, 2020;Izdihar & Widiastuti, 2020). Some investigations also examined the pattern of economic empowerment through Micro Waqf Banks (Arfin, 2021;Dewanti et al, 2021). Meanwhile, none of these analyses comprehensively focused on the realization of women empowerment through Islamic microfinance institutions in Indonesia.…”
Section: 2mentioning
confidence: 99%
“…Third is the provision of assistance or the distribution of funds to customers. BWM is an alternative that can be further improved to boost small and micro-economic development, as well as have an impact on the productive ability of women in decision-making (Dewanti et al, 2021). Najmudin et al (2019) examined the effect of BWM products such as ijarah, wakalah bil ujrah, and pesantren on women economic empowerment.…”
Section: Women Economic Empowerment Through Micro Waqf Banksmentioning
confidence: 99%
“…The majority of studies on BWM are related to the impact of BWM on the economy, as research conducted by Zayanie et al, (2019) Yeubun et al, (2021), Dewanti et al, (2021) and Apriliawan et al, (2021). Thus, research on the extent to which the application of joint liability-based financing in preventing the occurrence of non-performing financing is important to do.…”
Section: Scheme Of Bank Wakaf Mikromentioning
confidence: 99%